Bioaccumulation, elimination and metabolism in earthworms and microbial indices responses after exposure to decabromodiphenyl ethane in a soil-earthworm-microbe system. (15th November 2021) - Jiang, Lingling; Ling, Siyuan; Fu, Mengru; Peng, Cheng; Zhang, Wei; Lin, Kuangfei; Zhou, Bingsheng
Abstract: As a novel brominated flame retardant (NBFR), decabromodiphenyl ethane (DBDPE) has been poorly understood for the environmental fate and toxicity in terrestrial invertebrates. For the first time, the bioaccumulation, elimination, metabolism and detoxification of DBDPE in earthworms as well as its potential impacts on soil microbes were investigated. The results showed much higher DBDPE concentrations in casts than in earthworms. The bioaccumulation factor (BAF) and elimination rate constant (ke ) values were 0.028–0.213 (gdw, worm/gdw, soil) and 0.323–0.452 (day −1 ), respectively. The detoxifying enzymes (CYP450 and GST) could be induced by DBDPE within the range of exposure dosage, and the activities were significantly increased at 21 d ( p < 0.05). The results were identified by GC-ECNI-MS, and it showed that at least eleven unknown peaks were separately observed in the earthworms, which were the biotransformation products of DBDPE in earthworms. Additionally, the damages, including skin shrinkage, setae impairment, and intercellular vacuolization, were clearly observed by SEM/TEM. Based on these data, DBDPE could accumulate in earthworms, yet, with low bioaccumulation ability. Moreover, DBDPE exposure resulted in minimal harmful impacts on microbial activities including microbial biomass C (MBC), Microbial basal respiration (MBR), Urease (US) activity and fluorescein diacetate hydrolase (FDA) activity ( p < 0.05). Our findings would provide some essential information for interpreting the ecological risks of DBDPE in soil. Graphical abstract: Image 1 Highlights: DBDPE biotransformation occurred in earthworms with a low accumulation potential. CYP450 and GST were significantly induced by DBDPE. Damages in the microscopic structure of earthworms were clearly observed by SEM/TEM after exposed to DBDPE. DBDPE exposure resulted in the minimal negative effects on soil microbial activity. Abstract : This study explored the fate of decabromodiphenyl ethane in earthworms and microbial indices toxicity in a soil-earthworm-microbe system for the first time.